Surgical approaches to the calcaneus and the sural nerve: There is no safe zone. Issue 6 (December 2018) - Smyth, Niall A.; Zachwieja, Erik C.; Buller, Leonard T.; Miranda, Alejandro D.; Steinlauf, Steven D.
Highlights: Main trunk of sural nerve did not cross the path of the ELA in any specimen. Main trunk of sural nerve crossed the path of the STA in 2 specimens. At least one lateral calcaneual branch (LCB) of the sural nerve was identified in all specimens. ELA crossed the path of at least one LCB in 15 specimens (88%). Anastomotic branch of the sural nerve (AB) was present in 9 specimens and was crossed by the STA in every instance. Abstract: Background: Sural nerve related symptoms following the extensile lateral approach to the calcaneus (ELA) and the sinus tarsi approach (STA) are a known postoperative complication despite awareness of the course the sural nerve. While the main trunk of the sural nerve and its location relative to the approaches have been previously described, the nerve gives rise to lateral calcaneal branches (LCBs) and an anastomotic branch (AB) that may be at risk of injury. The purpose of this study was to describe the course of the sural nerve, its LCBs and the AB in relation to the ELA and STA. Methods: 17 cadaveric foot specimens were dissected, exposing the sural nerve, the LCBs and the AB. A line representing the ELA and STA incision was then created. It was noted if the line crossed the sural nerve trunk, any of the LCBs, and the AB, and at what distance they were crossed using the distal tip of the fibula as a reference. Results: The sural nerve was identified in all specimens, and the main trunk was noted to cross the path of the ELA in no specimens and the path of the STA in 2 (12%) specimens. At least one LCB of the sural nerve was identified in all specimens. The ELA crossed the path of at least one LCB in 15 specimens (88%). An AB was present in 9 specimens (53%). If an AB was present, this was crossed by the STA in every instance. Conclusions: The ELA and the STA traverses the path of either the main trunk of the sural nerve, the LCBs, or the AB in the majority of specimens, potentially accounting for the presence of sural nerve postoperative symptoms regardless of the approach used.